2019
DOI: 10.3389/fpls.2019.00008
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecules Selectively Modulate Iron-Deficiency Signaling Networks in Arabidopsis

Abstract: Plant growth requires optimal levels of iron (Fe). Fe is used for energy production, numerous enzymatic processes, and is indispensable for cellular metabolism. Recent studies have established the mechanism involved in Fe uptake and transport. However, our knowledge of Fe sensing and signaling is limited. Dissecting Fe signaling may be useful for crop improvement by Fe fortification. Here, we report two small-molecules, R3 and R6 [where R denotes repressor of IRON-REGULATED TRANSPORTER 1 (IRT1)], identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Transmission electron microscopy analyses of ftsh2 and ftsh5 leaves revealed, indeed, correctly-shaped chloroplasts in the green sectors, while the white sectors showed miss-shaped plastids with highly vacuolated organelle structures [ 6 , 9 ]. Furthermore, second-site suppressor screens aimed to identify mutations able to suppress the ftsh leaf variegated phenotype, so-called Suppressors of Variegation (SVR), allowed the identification of several nuclear genes encoding plastid-located proteins mostly involved in rRNA maturation, translation, protein folding and protein degradation [ 3 , 10 , 11 , 12 , 13 , 14 ]. Overall, these findings indicated that the differentiation of functional chloroplasts requires an optimal balance between the rate of plastid protein synthesis and the activity of the plastid protein quality control machinery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy analyses of ftsh2 and ftsh5 leaves revealed, indeed, correctly-shaped chloroplasts in the green sectors, while the white sectors showed miss-shaped plastids with highly vacuolated organelle structures [ 6 , 9 ]. Furthermore, second-site suppressor screens aimed to identify mutations able to suppress the ftsh leaf variegated phenotype, so-called Suppressors of Variegation (SVR), allowed the identification of several nuclear genes encoding plastid-located proteins mostly involved in rRNA maturation, translation, protein folding and protein degradation [ 3 , 10 , 11 , 12 , 13 , 14 ]. Overall, these findings indicated that the differentiation of functional chloroplasts requires an optimal balance between the rate of plastid protein synthesis and the activity of the plastid protein quality control machinery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in Fe acquisition and distribution have been previously identified by the reverse genetic strategy through expression studies in mutants and transgenic genotypes in Arabidopsis and tomato (Kobayashi and Nishizawa 2012;Connort et al 2017). For Fe uptake, coumarins, facilitated by the PDR9/ABCG37 transporter (Fourcroy et al 2014;Tsai and Schmidt 2017) and protons, mediated by a plasmalemma P-Type ATPase (AHA2) (Santi and Schmidt 2009) are pumped to the rhizosphere to increase Fe 3+ solubility (Kailasam et al 2019). The secretion of coumarins (derived from precursors of the phenylpropanoid pathway) is dependent on specific β-glucosidases (Clemens and Weber 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In plastids, several thousand Fe atoms are stored per ferritin molecule (Briat et al 2010). Regulation of iron homeostasis is essential and it occurs through the action of positive and negative regulators (Kailasam et al 2019). Iron uptake and transport is coordinated by transcription factors including FER in tomato (FIT in Arabidopsis) and many others from the basic Helix-Loop-Helix (bHLH), MYB and WKY families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that nucleosides and nucleobases can pass plant membranes via several transport proteins 27 , and plant roots can take up and metabolize nucleosides for degradation, or utilize them in more efficient salvaging processes 28 . However, the extracellular nucleotide ATP has been identified as a plant-surface signaling molecule, with functions in stress and wounding responses of roots 29 31 .…”
Section: Discussionmentioning
confidence: 99%